A Decision Support System for Operating Room scheduling. (October 2015) - Dios, Manuel; Molina-Pariente, Jose M.; Fernandez-Viagas, Victor; Andrade-Pineda, Jose L.; Framinan, Jose M.
Highlights: We present a Decision Support System for OR scheduling. We propose an MILP model and several heuristics to address the decision problem. We describe the advantages and results obtained from the implementation of the DSS. Abstract: In this paper we present a Decision Support System (DSS) for surgery scheduling which is currently in use in several Surgical Units in one of the largest hospitals in Spain. This system embeds a number of optimization procedures (both exact and approximate) to support decisions related to the assignment of dates and Operating Rooms to the interventions of patients in a waiting list. The system is capable of producing a medium-term – i.e. up to six months – plan in order to estimate the week in which each patient would be intervened, so that the material and human resources needed for their intervention can be arranged. A short-term (two weeks) plan can be obtained to determine optimal or quasi-optimal intervention dates taking into account the surgical resources, patients' availability, as well as a number of specific constraints and features imposed by the Hospital's Managers (such as e.g. the maximum number of ORs in which a surgeon can intervene within a shift). The proposed DSS allows users to manually modify the plans in order to adapt them to last-minute changes via an interactive graphical user interface. The system has been successfully employed for surgery scheduling.